ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT PENGGUNA E-LEARNING (CLASSROM) DI SMK NEGERI 7 JEMBER MENGGUNAKAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 2 (UTAUT 2) - Yunita, Rosiana Dwi (Informatics, Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACTTo measure the factors that influence the acceptance of technology, then the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model is used where there is a change in the moderate variable, namely the student variable previous education and gender. Testing the model in this study using software SmartPLS. The results in this study are the factors that influence user intentions in using e-learning. It was found that the influencing factors were Performance expectancy is also referred to as performance expectations which have an influence on positive and significant on behavior intention in the behavior of using e-learning by student. This factor is proven to be the influence of students' intentions in using technology at SMK Negeri 7 Jember. Keywords: User Acceptance, E-learning, Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2), Gender, Previous education Students ABSTRAKUntuk mengukur faktor-faktor yang mempengaruhi penerimaan terhadap teknologi, maka digunakan model Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) yang dimana terdapat perubahan pada variabel moderat yakni variabel student previous education dan gender. Pengujian model dalam penelitian ini menggunakan software SmartPLS. Hasil dalam penelitian ini adalah faktor-faktor yang mempengaruhi niat pengguna dalam menggunakan e-learning. Diperoleh bahwa faktor yang berpengaruh adalah performance expectancy disebut juga sebagai ekspektasi kinerja dimana memiliki pengaruh positif dan signifikan terhadap behavior intention dalam perilaku penggunaan e-learning oleh siswa. Faktor inilah yang terbukti sebagai pengaruh niat siswa dalam menggunakan teknologi di SMK Negeri 7 Jember. Kata Kunci: Penerimaan Pengguna, E-learning, Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2), Jenis Kelamin, Pendidikan Sebelumnya Siswa